Heterogeneous adaptability: Learning, cash resources, and the fine-grained adjustment of misaligned governance - MARTIN, Xavier (Institutional Knowledge at Singapore Management University, 2024)
Research Summary: When can a firm make fine-grained adjustments to misaligned subsidiary governance? We examine whether and under what conditions a firm will adapt the equity stake it owns in a subsidiary, enabling improved alignment of the stake with the uncertainty in the local environment. We predict that the rate of adaptation of misaligned equity stakes depends on the experiential and vicarious learning from which the firm can draw, and that these learning effects are contingent on possessing fungible slack resources, specifically cash. Using a sample of 726 Japanese-foreign subsidiaries established in 38 host countries over a 21-year period, we find support in line with our predictions. Overall, this study explicates heterogeneous adaptability in subsidiary governance and similar strategic tasks. Managerial Summary: Whether due to suboptimal choices or changing conditions, firms must sometimes change how they relate with and control their subsidiaries. Whereas much research has addressed adaptation in the form of discrete changes in ownership mode, we examine under what conditions a firm can make fine-grained adjustments to misaligned subsidiary governance. We argue that a firm can learn to make such adjustments, not only from its own experience but also vicariously by observing other firms in the same foreign environment. Furthermore, we consider whether cash is a valuable resource for this purpose. Overall, this study shows how firms can pursue strategic adaptation in subsidiary governance and related tasks.